Implied Representations of Alevism and Alevis in Yeşilçam Cinema (Journal of Alevism-Bektashism Studies, 2023)
From the beginning until the 1950s, Turkish filmmakers were not able to discuss historical, social and political issues or reflect them on the silver screen. The reflections of the changing sociological and political climate in cinema since the 1950s began to manifest themselves in the 1960s, and especially sociological elements became more visible on the silver screen. Alevi Bektashis, who can be considered as a collective community in the context of belief and identity in Turkey, have either been ignored throughout the history of Turkish cinema, or have had great difficulty in finding a place for themselves on the silver screen. The social, political, cultural and economic developments that began in the 1950s were also reflected in cinema. In this context, Alevis and Alevism have started to gain public visibility in various fields, especially since the second half of the 1960s, and cinematic representations of this situation have been seen, albeit very limited. Alevi-Bektashis, an invisible element of Turkish cinema, began to be represented in various films, albeit implicitly, during the Yeşilçam cinema period. In this study, Yeşilçam cinema has been subjected to a periodisation covering the years from the mid-1950s to 1980. The aim of the study is to reveal the representation of Alevi Bektashi belief and identity on the silver screen in this period and to express the approaches of the directors to Alevism in a descriptive way through the screening method. Thus, it is claimed that Alevi Bektashi faith is represented in Yeşilçam cinema, albeit implicitly without mentioning its name, that some rituals of Alevi Bektashi faith are reflected on the silver screen, and that this representation is more numerous but still very insufficient, unlike the films in the previous studies.